Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/pds.1558
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between administrative databases and medical charts for pregnancy‐related variables among asthmatic women

Abstract: Pregnancy-related variables recorded in administrative databases or derived from algorithms based on two or more databases were found to be highly valid as compared to the medical chart among asthmatic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 34 publications
(28 reference statements)
2
109
0
Order By: Relevance
“…9,27,28 Einarson and colleagues found no statistically significant association between venlafaxine use during pregnancy and the risk of spontaneous abortion among 150 women. 18 Two recent reviews reported contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,27,28 Einarson and colleagues found no statistically significant association between venlafaxine use during pregnancy and the risk of spontaneous abortion among 150 women. 18 Two recent reviews reported contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Nevertheless, our findings are similar to those of Einarson and colleagues, who showed that overall antidepressant use during early gestation increased the risk of spontaneous abortion by 63%. 18 Much remains unclear with regard to the exact mechanism of action, although it has been suggested that the effect of selective serotonin reuptake inhibitors on spontaneous abortion is probably mediated by a serotonergic mechanism.…”
Section: 12mentioning
confidence: 99%
“…Data recorded in these three databases have been validated previously. [8][9][10] Studies involving pregnant women insured by the RAMQ for their medications have been shown to generate valid risk estimates. 7 Our study was approved by the Centre hospitalier universitaire Ste -Justine Ethics Committee, and the linkage between databases was approved by the Commission d'accès à l'information du Québec.…”
Section: Methodsmentioning
confidence: 99%
“…We also used physician-based diagnoses and records of procedures related to spontaneous abortion, which limited the potential for detection and misclassification biases on outcome status. Gestational age, validated by Vilain and coworkers, 9 was obtained from hospital charts on the index date, allowing us to calculate the exact timing of exposure to nonaspirin NSAIDs during pregnancy. We adjusted our results for indication for the use of nonaspirin NSAIDs by adjusting for variables such as history of rheumatoid arthritis and systemic lupus, and for the duration of exposure in the year before pregnancy; we further adjusted for history of planned and spontaneous abortions.…”
mentioning
confidence: 99%
“…We determined the day of the last menstrual period (defined as the first day of gestation) using data on gestational age, which was validated against data in patient charts and ultrasound measures. 10 Prospective follow-up data were available from 1 year before the first day of gestation, during pregnancy and until December 2009. The data sources for this study included RAMQ (diagnoses, medical procedures, socioeconomic status of women and prescribers), the province's Public Prescription Drug Insurance Plan database (drug name, start date, dosage and duration), MED-ÉCHO (in-hospital diagnoses and procedures, and gestational age) and the Institut de la statistique du Quebec (patient sociodemographic data and birth weight).…”
Section: Data Sourcesmentioning
confidence: 99%